IMPACTS OF BILINGUALITY ON STUDENTS’ ACADEMIC WRITING SKILL: ADDITIONAL EVIDENCE - Sugiharto, Setiono (Universitas Pendidikan Indonesia, 2015)
A plethora of published studies has convincingly demonstrated that bilingual students excel academically than their monolingual counterparts. Apparently, findings of these studies have been used to counterattack the long-standing assumption that the psychological state of being able to access to more than one linguistic code (bilinguality) is more deleterious than beneficial. With new insights accumulating in support of bilinguality, the present study extends the findings of the previous ones, arguing that bilingualiaty positively affect studentsâ€™ coping strategies in academic writing tasks. Forty-eight students (24 monolinguals and 24 bilinguals) were assigned with a writing prompt with a topic related to an academic issue. Both quantitative and qualitative analysis were employed. Â Results from the quantitative analysis showed that the bilingual group exhibited more writing gains than the monolingual one. Qualitative analysis revealed that bilingual students employed more varied and richer coping strategies that their monolingual counterparts. With this additional evidence, this study suggests that there is an interconnected link between bilinguality and coping strategies in writing.